2021
DOI: 10.1093/ehjacc/zuaa034
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of circulating microRNAs compared to high-sensitivity troponin T for the detection of non-ST-segment elevation myocardial infarction

Abstract: Aims To assess the diagnostic value of microRNAs (miRNAs) for the detection of non-ST-segment elevation myocardial infarction (NSTEMI). Methods and results A total of 1042 patients presenting between August 2014 and April 2017 to the emergency department with the suspected acute coronary syndrome were included. Non-ST-segment elevation myocardial infarction was diagnosed per criteria of the fourth Universal definition of myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…These findings emphasize that miRNAs owe the potential of improving the current strategy of MI-diagnostics, which incorporates the evaluation of serial cTn’s concentrations and their kinetic [ 3 ]. In contrast, it has been recently demonstrated that single miRNAs and a signature of best performing miRNAs can fail adding diagnostic accuracy to cTn serial measurements for detection of NSTEMI [ 32 ]. Both studies show relevant differences in terms of study design [ 32 , 72 ], wherefore miRNAs potential for clinical implementation still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings emphasize that miRNAs owe the potential of improving the current strategy of MI-diagnostics, which incorporates the evaluation of serial cTn’s concentrations and their kinetic [ 3 ]. In contrast, it has been recently demonstrated that single miRNAs and a signature of best performing miRNAs can fail adding diagnostic accuracy to cTn serial measurements for detection of NSTEMI [ 32 ]. Both studies show relevant differences in terms of study design [ 32 , 72 ], wherefore miRNAs potential for clinical implementation still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been recently demonstrated that single miRNAs and a signature of best performing miRNAs can fail adding diagnostic accuracy to cTn serial measurements for detection of NSTEMI [ 32 ]. Both studies show relevant differences in terms of study design [ 32 , 72 ], wherefore miRNAs potential for clinical implementation still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 However, they currently do not improve the diagnosis of acute MI on top the currently available methods and the turnaround time is long. 8 Therefore, RNAs in ischaemic heart disease may be more informative to guide therapies after the acute phase, e.g. to improve the prediction of left ventricular (LV) dysfunction post-MI, predict recurrent ischaemic events, and eventually guide new cardioprotective therapies.…”
Section: Rationale and Clinical Need For Rna Biomarkersmentioning
confidence: 99%
“…In consideration of their roles, steadily growing research in life science of the expression pattern of cardiac tissue reveals that microRNAs (miRNAs/miR) are up-or downregulated during myocardial injury, showing their potential as biomarkers for AMI and ischemia-reperfusion injury (I/R) [17,18]. Accordingly, the gamut of new evidence lays out the potential role of miRNAs as novel biomarkers in acute and chronic cardiovascular diseases such as stable CAD [17,[19][20][21][22], acute coronary syndromes (NSTEMI/STEMI) [23][24][25][26], or heart failure (HF) and cardiac remodeling secondary to MI [27,28].…”
Section: Introductionmentioning
confidence: 99%